Molecular Materials and Functional Polymers 2001
DOI: 10.1007/978-3-7091-6276-7_11
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic Bands in the Spectra of Some Organic-Inorganic Hybrid Compounds Based on Metal Halide Units

Abstract: Summary. The optical absorption, photoluminescence, and photoconductivity spectra of some compounds of the formulas [R(CH2)nNH3IxMyXz, [R(CH2)nNH(CH3hlxMyXz, [R(CH2)nS(CH3hlxMyXz' [R(CH2)nSC(NH2hlxMyXz, and [R(CH2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
1
8
0
1
Order By: Relevance
“…32 In this work we report a simple, instant and low cost method for the fabrication of a LED device constructed by a single active layer, composed of 0D, 3D and 2D HOIS blend. This blend containing specific (0D/3D):2D molar ratio, manifests simple, yet obvious energy transfer effects, 33 as these have been seen in semiconductor materials like CsPbBr3, [34][35][36] while similar phenomena in LED have been observed in recent publications. 37,38 LED device, presented herein, can function at room temperature, ambient air and low voltages while the EL emission is visible by naked eye.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…32 In this work we report a simple, instant and low cost method for the fabrication of a LED device constructed by a single active layer, composed of 0D, 3D and 2D HOIS blend. This blend containing specific (0D/3D):2D molar ratio, manifests simple, yet obvious energy transfer effects, 33 as these have been seen in semiconductor materials like CsPbBr3, [34][35][36] while similar phenomena in LED have been observed in recent publications. 37,38 LED device, presented herein, can function at room temperature, ambient air and low voltages while the EL emission is visible by naked eye.…”
Section: Introductionsupporting
confidence: 67%
“…In the past, it has been observed that even if the OA of the lowest Eg moiety, in a similar blend, is minimum, it is possible to have PL only at that lowest Eg energy. 33 As a result, all energy observed was being transferred from the high energy states to the lowest, by virtue of Forster like energy transfer, where superradiance effects certainly must be taken into account as these link the excitonic wave functions along with the radiation field. 44,45 However, in this previous total energy transfer observation, the materials had been literally grinded together to form a set of well split and adjoined quantum entities.…”
Section: Resultsmentioning
confidence: 99%
“…Such excitonic peak energy is attributed to the PbI 3 chain network in several studies. 46,47 Analyzing the diffuse absorbance data, we get an E g at 3.1 eV (interception of extrapolated line with energy axis in Figure 5). Such high band gap values are accordingly estimated in other 1D perovskites such as [tetrabutylammonium][PbI 3 ] 48 (2.76 eV), CsPbI 3 49 (3.05 eV), or even (CH 3 ) 3 NHGeI 3 50 (2.88 eV).…”
Section: Chemical and Thermal Stabilitymentioning
confidence: 99%
“…A schematic QW picture was introduced for layered perovskites yielding a simple and efficient framework to perform analogies with classical semiconductor heterostructures. ,, Progress on the understanding of their electronic structures was strongly connected to detailed experimental investigations of their excitonic properties. Moreover, D. Mitzi and co-workers obtained important conceptual advances, developing a technological approach for tin-based layered halide perovskites leading to the demonstration of transistor devices and to impressive anisotropic carrier transport properties. Researchers from Greece ,,,,, and Japan ,,,, ,, were the other most important contributors to the field at its early stage. The vast majority of the studies on low dimension halide perovskite structures were initially dedicated to monolayered systems such as A′ 2 BX 4 compounds (where A′ is typically an extended nonconjugated primary ammonium cation, R-NH 3 + ).…”
Section: Introductionmentioning
confidence: 99%